Anatomical and Visual Outcomes of Macular Hole Surgeries: Doi: 10.36351/pjo.v41i2.1872 - Rizvi, Syed Ali Afsar; Naz, Saliha; Rizvi, Syed Fawad; Fatima Tariq; Muhammad Kaunain Ghoghari (Pakistan Journal of Ophthalmology, 2025)
Purpose: To determine the anatomical and visual outcomes of macular hole surgeries in patients with full thickness macular holes in a tertiary care center of Pakistan. Study Design: Interventional case series. Place and Duration of Study: LRBT tertiary teaching eye hospital Korangi, Karachi, from January 2023 to July 2023. Methods: Twenty-four eyes of 24 patients were included by convenient sampling. Patients with Gass stage 2,3 and 4 were included in the study after an informed consent.The study omitted holes with stage 1, macular cysts, and secondary macular holes. Visual acuity of the patients was recorded in decimal notations based on Snellen’s chart. OCT was done in all patients. after peri-bulbar anesthesia, 25G pars plana vitrectomy was performed with C3F8 gas as internal tamponade. All individuals were followed up on day 1, week 1, 6, 12 and 24. OCT images were taken to see hole closure. The paired sample t-test was used to compare the difference of pre and post operative VA. P-values less than 0.05 were considered statistically significant. Results: Out of 24 eyes, 62.5% were males and 37.5% were females.The mean age of the patients was 65.3±9.1 years. Visual acuity significantly improved after surgery with p- value of <0.05. Conclusion: Macular hole surgery using 25G pars plana vitrectomy with C3F8 gas tamponade yielded favorable anatomical and visual outcomes in patients with full-thickness macular holes.